A صاحبِ تفسیر ِصدیقی کا عصری مسائل کے حل اور کلامی مباحث میں طرزِاستدلال: تجزیاتی مطالعہ: Sahib-e-Tafseer-e-Sadiqi’s style of reasoning in contemporary problem solving and discourse discussions: an analytical study - ud-Din , Hafiz Fareed-; Shahid, Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
Holy Qur’an is the last revealed book of Allah Almighty.The explanation of its verses started from the time of last apostle and it will continue till the day of resurrection. The land of Indo Pak sub-continent is much fertile regarding the personalities who worked for the interpretation of the last revealed book. In this research paper characteristics and methodology of Tafseer-e-Siddiqui are discussed, especially Theological Discussions of exegesis are analysed. Moulana Abdul Qadeer Siddiqui was a renowned theologian of Hyderabad Dakkan. He spent his whole life in learning and teaching Islam. His work on Tafseer-e-Qur’an is a great contribution for Quranic understanding. In this Tafseer the writer has also consulted books of other religions.He criticized orientalists but with politeness. There is dire need to spread this contribution of Moulana Siddiqui among the Muslims and especially the students of educational institutions. Key Words: Holy Qur’an, Hadith, Orientialists, Chiristianity, Judaism.